The impact of the COVID-19 pandemic on physical activity and sleep among healthy adults: a systematic review and meta-analysis - Cui, Dandan; Zhang, Xiangning; Guo, Jianwei (Frontiers in Psychology, 2023)
Background: The COVID-19 pandemic has had a significant impact on physical and mental health, while physical activity and sleep are two important indicators of the impact that have been explored in recent research. However, the results of studies with different measurement methods and populations with different levels of physical activity have been diverse in that physical activity and sleep are affected by the COVID-19 pandemic in some studies but not in others. Our study is to investigate the impact of the COVID-19 pandemic on physical activity and sleep and the role of measurement methods and populations on results. Methods: PubMed, Web of Science, and CNKI databases were used to search for related studies systematically. Study characteristics and data on physical activity and sleep were collected and analyzed from each included study. Standardized Mean Differences (SMDs) with 95% confidence intervals (CIs) were used to estimate pooled effect sizes. Results: 13 articles were included in the systematic review, 11 of which were included in the meta-analysis. We found that moderate to vigorous physical activity (MVPA) time was 0.33 (95%CI 0.07 to 0.59) and sleep quality was 0.37 (95% CI 0.21 to 0.53) declined, while sleep duration was -0.24 (95% CI -0.28 to -0.20) increased during the lockdown; overall physical activity time had no significant difference (p=0.07) during the lockdown. The “Wearables” subgroup has no heterogeneity (p=0.89, I2=0) in sleep duration, while MVPA time measured by subjective scales was not significantly changed. The “elite athletes” subgroup has lower heterogeneity (p=0.69, I2=0) in sleep duration than general adults, while the results of sleep quality for population subgroups were significant and there was no heterogeneity within either. Conclusion: The COVID-19 pandemic had a significant impact on MVPA time, sleep duration, and sleep quality, instead of overall physical activity time among healthy adults. The results of MVPA time and sleep duration are greatly influenced by the measurement methods, and sleep behavior differs among populations with varying physical activity levels. Thus, when researching physical activity, especially MVPA time, should consider measurement methods, and more attention should be given to differences in populations when researching sleep behavior.